2016
DOI: 10.1186/s40661-016-0034-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing in a gynaecological oncology care in developing countries—knowledge, attitudes and perception of Nepalese clinicians

Abstract: BackgroundGenetic testing for an inherited susceptibility to cancer is an emerging technology in medical practice. Little information is currently available about physicians’ attitudes towards these tests in developing countries.MethodsWe conducted an email survey of Nepalese physicians practicing in academic and non-academic settings in Nepal, regarding knowledge, attitudes and perception towards genetic testing for gynaecologic cancer.ResultsResponses were received from 251 of 387 practitioners (65%). Only 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Although there have been recent advances in the availability of genetic testing in many developing countries, there is disparity in skills and knowledge among the health care providers regarding the availability of modern scientific tools, and recognition of the benefits of genetic testing for gynaecological cancers. As such, there is a great need for the introduction of further genetic counselling education and hereditary cancer services for gynaecological care in Nepal [ 35 ]. However, multiple barriers need to be overcome.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there have been recent advances in the availability of genetic testing in many developing countries, there is disparity in skills and knowledge among the health care providers regarding the availability of modern scientific tools, and recognition of the benefits of genetic testing for gynaecological cancers. As such, there is a great need for the introduction of further genetic counselling education and hereditary cancer services for gynaecological care in Nepal [ 35 ]. However, multiple barriers need to be overcome.…”
Section: Resultsmentioning
confidence: 99%
“…The information applies to a relatively small number of patients in any practice, and the evidence base changes rapidly, making it difficult for all but the most specialized providers to stay up-to date. In our previous study [ 35 ] it was found that approximately 46% of all clinicians felt prepared to answer patient’s questions about genetic testing for gynaecologic cancer. However, while 94% of gynaecologic oncologists felt prepared, only 47% of gynaecologists and 26% of other clinicians did so, despite 86% of gynaecologists and 71% of other clinicians reporting that patients had asked questions about genetic testing [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations